2022
DOI: 10.1111/cen.14685
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disorders in obstructive sleep apnoea syndrome: A bidirectional relationship

Abstract: Obstructive sleep apnoea (OSA) is a common disorder characterized by recurrent episodes of apnoea or hypopnea due to total or partial pharyngeal collapse and temporary upper airway obstruction during sleep. The prevalence of OSA is increasing and currently affects about 30% of men and 13% of women in Europe.Intermittent hypoxia, oxidative stress, systemic inflammation, and sleep fragmentation resulting from OSA can provoke subsequent cardiometabolic disorders. The relationships between endocrine disorders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 84 publications
(188 reference statements)
0
17
0
Order By: Relevance
“…de Raaff et al 27 concluded that severe apnea (AHI ≥ 30) before surgery was a predictive factor of OSA persistence. Yanari et al 4 also observed that pre-operative AHI was an independent prognostic factor of OSA persistence. In Ravesloot et al, 29 age was not a predictive factor of OSA remission, unlike the results from de Raaff et al 27 in which older age predicted OSA persistence.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…de Raaff et al 27 concluded that severe apnea (AHI ≥ 30) before surgery was a predictive factor of OSA persistence. Yanari et al 4 also observed that pre-operative AHI was an independent prognostic factor of OSA persistence. In Ravesloot et al, 29 age was not a predictive factor of OSA remission, unlike the results from de Raaff et al 27 in which older age predicted OSA persistence.…”
Section: Resultsmentioning
confidence: 90%
“…A meta-analysis of studies that followed patients up to 24 months indicated that the remission rate of T2D was 63.5%–82%. 46 Since T2D is a risk factor for OSA, 4 persistence of T2D could be an explanation for OSA persistence after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a prevalent and under-diagnosed disorder characterized by repeated closure of the upper airway tract during sleep, resulting in sleep fragmentation and intermittent hypoxia [ 4 ]. This disorder not only causes daytime drowsiness, but also exacerbates cardiovascular issues, obesity-related metabolic dysfunction, systemic inflammation, and a weakened immunological response to infection [ 5 , 6 ]. Whether OSA is a risk factor for COVID-19, particularly severe COVID-19, has long been a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is worth noting that patients with moderate-to-severe OSA have a higher incidence of asymptomatic cerebrovascular disease than those with less severe OSA (Nishibayashi et al, 2008). OSA is also affecting the metabolism of endocrine hormone levels, and patients with OSA are at a higher risk of developing certain endocrine and metabolic diseases (Akset et al, 2022). The relationship between endocrine disorders and OSA is complex and bidirectional.…”
Section: Introductionmentioning
confidence: 99%